TEACHING USING THE ARDUINO PLATFORM APPLIED TO THE CONCEPT Of IoT AS SUPPORT TO MICROCONTROLLER CLASS - de Oliveira, Victor Inácio; Martins, Hugo Magalhaes; Rosa, Flávio Nastari; dos Santos, Jadir Perpétuo; de Morais, Diogo Martins Gonçalves; Junger, Alex Paubel (South American Development Society Journal, 2021)
Resumo With the emergence of the concept of IoT - the Internet of Things, it has become virtually impossible not to contextualize it in programming classes of electronic devices, such as processors and microcontrollers today. Thus, this work shows the analysis of a teaching methodology aimed at including in one of these courses an introduction to IoT, not excluding traditional hardware clarifications, such as the use of old microcontrollers such as 8051 (INTEL) and/or PIC (Microchip), thus not impairing, initial objectives proposed. The ARDUINO Platform, a powerful and free development tool, was used to support the implementation of this proposal. This system allows a hardware abstraction through modules called Shields for industrial applications and can run communication algorithms in real-time, allowing to embark as a product some of the concepts of IoT. This article discusses the experience obtained with the use of such methodology applied to the microcontrollers class in a Course Technology in Industrial Automation of a Federal School, synthesized after the analysis of questionnaires to teachers and students involved in this course. The results of this methodology were positive, motivating the desire to better understand new hardware devices and how to program them, besides creating an innovative spirit in the projects of the graduates of this course concerning previous classes.